Palace, political party, and power a story of the socio-political development of Malay kingship - Kobkua Suwannathat-Pian 1944- (NUS Press, 2011)
"Traces the history of Malay Rulers in the Malay Penisula from the late colonial period to the first decade of the 21st century, considering the implications of their decline under colonial rule and the role of the Japanses Occupation in defining Malay identity. After independence in 1957, the Malay Rulers were compelled to embrace Westminster-style constitutional monarchy, under which their role is largely symbolic and affairs of the nation are run by Parliament and the executive branch. A key element of the postwar period was the relation between the Malays and their Rulers, and the way UMNO--the United Malays National Organisation--positioned itself as the "official" voice of the Malays and the Rulers. This postwar settlement underwent a significant change after the shocking outcome of the March 2008 General Election, which weakened UMNO's hold on power. The Malay Rulers responded by 'reinventing' themselves as active players in the affairs of the nation and recovered some of their traditional rights. Socio-political developments since the departure of Prime Minister Mahathir Mohamad have worked in favor of a royal resurgence, and the Rulers have become an increasingly vocal element in national politics."